Forming a form and studying the formation process - Zhaskilenova A.K. Жаскиленова А.К.; Sharinova G.S. Шаринова Г.С. (Рroblems of engineering and professional education, 2022)
The article discusses ways to form the shape of a suit. In connection with the intensification of competition in the consumer goods market, attempts to demonstrate the effectiveness of creative labor have increased. He developed a series of methods, approaches and methodologies that rationally organize the search for new solutions. In the process of designing a suit, The Shape of clothing is at the forefront. The importance of the article is to determine the quality and compositional solution of manufactured products using combinatorics in accordance with modern fashion trends, to model models of clothing and shape patterns for women. In the process of forming a form, changes occur without a process that meets the requirements of the time. In some cases, the formation of a format without taste, without studying the requirements of society leads to poor quality and disharmony of the costume. A designer or stylist must not only create an object or pattern that is a physical object, but also know the complex structure of the semiotic system of the costume and the laws of human vision. The suit is considered as a means of visual communication of people, a difficult object for its universality and belonging to the general. It is noted in the article that several research works were carried out to solve these problems.